The Influence of Local Culture, Cuisine, and Natural Scenery on Tourist Satisfaction at Gili Meno Beach, West Nusa Tenggara Indonesia - Sutrisno; Widodo, Slamet (Sinergi International Journal of Economics, 2024)
This research investigates the influence of local culture, culinary experiences, and natural scenery on tourist satisfaction at Gili Meno Beach, West Nusa Tenggara, Indonesia. Employing a quantitative research design using Structural Equation Modeling Partial Least Squares (SEM PLS) method, the study involved 160 tourist respondents visiting the destination. The findings reveal that local culture (β = 0.05, p < 0.05), culinary experiences (β = 0.02, p < 0.05), and natural scenery (β = 0.02, p < 0.05) significantly influence tourist satisfaction. These results underscore the importance of cultural elements, local cuisine, and natural beauty in creating positive experiences for tourists at the destination. Managerial implications include developing more effective marketing strategies to enhance destination appeal and improve visitor experiences, as well as emphasizing cultural and environmental preservation to support sustainable tourism. This research contributes significantly to tourism literature by exploring key factors influencing tourist satisfaction in unique contexts such as Gili Meno Beach.